Fractal assessment analysis of China's air-HSR network integration - Lu, Mengyuan; Jimenez Perez, Edgar; Mason, Keith; He, Yin (Elsevier, 2024)
High-speed rail (HSR) has emerged as a significant mode for intercity transport in several countries, particularly China, setting an environment that may promote integration between air and HSR networks. To better measure the current level of integration of China's air-HSR intermodal network and identify implementation issues, this paper establishes a novel assessment framework that considers three primary areas: service capability, network connectivity and transfer potential. The framework is based on a comprehensive literature review of network measurement and assessment methodologies. Then, fractal theory is used to establish an assessment model that associates the fractal dimension to the level of intermodal integration, which can serve as an important complement to traditional weighting methods. The model and framework are applied to the 10 cities in China with the potential for air-HSR integration. The results show that international hub airports, together with their closest HSR station, do not necessarily perform at a higher integration level than regional hubs. The paper also proposes policy and practical recommendations to enhance air-HSR network integration levels from service supply, network coordination and transfer design perspectives.
Keywords: Air-high speed rail integration; Network connectivity; Fractal assessment; Assessment index